PENDIDIKAN KARAKTER MELALUI PENDIDIKAN AGAMA ISLAM DI ERA REVOLUSI DIGITAL - Ayu Lestari Dalimunthe; Zaianal Efendi Hasibuan; Toib Lubis (Yayasan Baitul Hikmah al-Zain, 2025)
As technology becomes more advanced, humans must optimize their minds and ethics. Education is essential to generate intelligent and moral generations. Islamic religious education serves as a source of truth values of power that can produce the desired action. Character education is a necessity of the Indonesian state. This study investigates the teaching of Islam in the era of the digital revolution. This research uses qualitative methods. with the type of library research or research library. Researchers analyze written literature, which consists of books, research journals and prosiding seminars. According to this study, the values of religion, Pancasila, culture, and national education purposes are the source of character education in Islamic education. In Islamic religious education, impementation of character is carried out through teaching, uniformity, customization, coercion, and punishment to build the character of the student.